Cultural Belief of Petang Megang Ritual with Self Actualization on Malay Community, Pekanbaru City-Riau - ., Suroyo; Putra, Bima Maulana; Ibrahim, Bedriati (Udayana Journal of Social Sciences and Humanities; Vol 5 No 2 (2021): UJoSSH, September 2021, 2021)
Petang Megang is a ritual known as mandi balimau, Balimau Kasai, Potang Balimau, Potang Mogang, Balimau, Belangiran, or Pangir . It is conducted to greet the holy month of Ramadan in Malay community in Riau. The cultural belief of the Malay population in Pekanbaru towards the Petang Megang ritual can be linked to self-actualization, which can form the Malay community's character. As a cross-disciplined research, this study is qualitative based on structured interviews and observations about cultural ideas and self-actualization. Moreover, it has been linked to several fields such as anthropology, cultural studies, and religion. Based on the interview and observation conducted during the data collection process, it is known that Petang Megang involves many people starting from the bath preparation process to food serving after visiting the graves. This  comprises qualities that characterize Malay society’s actualization, such as unity, mutual collaboration, inventiveness, low self-esteem, ethics, and tolerance. Furthermore, this ritual has a psychological impact on the Malay community of Pekanbaru City with an attitude of humility, help, cooperation, and a sense of togetherness and tolerance. The Malay culture's belief in the Petang Megang ritual has a meaning as well as a philosophical value that characterizes the character as the Malay's actualization.   Keywords : Cultural Belief, Malay Community, Petang Megang Ritual, Self-Actualization.